Climate adaptation, urban regeneration and brownfield reclamation: a literature review on landscape quality in large-scale transformation projects - Oudes, Dirk; Stremke, Sven (Landscape research, 2020)
The transition to renewable energy is a powerful driver for large-scale landscape transformation. Environmental design is increasingly engaged in this transition, but little is known about purposefully designed renewable energy landscapes. To improve the design of large-scale energy landscapes we reviewed the literature on three innovative large-scale landscape transformations: Room for the River Nijmegen-Lent (The Netherlands), Queen Elizabeth Olympic Park (UK) and Freshkills Park (USA). We analysed 61 papers on landscape quality and the role of design, governments and participation. Concerning landscape quality, literature reports on functionality and certain aspects of experience rather than firmness (future values) of the transformation. While designers played an important role in large-scale landscape transformations, local governments seem not to be in control of the decision-making and participation was limited. The three cases illustrate how executed projects influence the discourse on landscape transformation and provide valuable insights for the design of renewable energy landscapes.